A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha: Fulgoromorpha: Delphacoidea: Cixiidae) from the cloud forest in Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2024)
A new species of Myxia is described from light collecting in Villa Blanca, Costa Rica. The new species possesses an unusual large areolet on the anterior portion of the vertex. Maximum Likelihood analyses based on the 18S rRNA gene, D9–D10 expansion region of the 28S gene, H3 gene and 5’ region of the COI gene support the monophyly of Myxia, with the new species nested deeply within the genus.